The influence of HF discharge on plasma parameters of gas source with incandescent cathode - Shariy, S.V.; Yuferov, V.B.; Tkachova, T.I.; Svichkar, A.S.; Shvets, M.O.; Tkachov, V.I. (Вопросы атомной науки и техники, 2015)
An experimental study of the influence of HF power and configuration of the magnetic field on the plasma parameters of the gas source with incandescent cathode was carried out. It is shown that the application HF power into discharge results in reduction of electron temperature. For discharge in decreasing magnetic field the radial distribution of the plasma density in the axial region is more uniform compared with increasing magnetic field.